Myocardial Iba1, MHC class II, and CD3 are diffusely increased in canine myocarditis: A step toward antemortem myocarditis diagnostics. Issue 5 (September 2022) - Vu, Kristina; Wikel, Vanessa; Molesan, Alex; Mudrak, Erika; Kelly, Kathleen
Canine myocarditis is a rare but serious health concern, potentially causing heart failure and death. Antemortem diagnosis is hampered by the numerous causes, nonspecific course, and dearth of diagnostic criteria. Currently, definitive diagnosis can only be made after death. The current human diagnostic gold standard is endomyocardial biopsy pairing cardiac histopathology with immunohistology to enhance detection of often-multifocal disease. We evaluated immune response markers in the canine heart to establish similar immunohistologic criteria. We hypothesized that myocardial major histocompatibility complex class II (MHCII), cluster of differentiation 3 (CD3), and ionized calcium binding adapter molecule 1 (Iba1), markers increased in human myocarditis, would be increased in canine myocarditis cases. Archived paraffin-embedded myocardial tissue from 22 histopathologically confirmed cases of adult and juvenile myocarditis and 23 controls was analyzed by immunohistochemistry for MHCII, CD3, and Iba1, and the fraction of myocardium with labeling was determined. All 3 markers were significantly increased compared with controls across the entire section: Iba1, 10.1× ( P < .0001, Mann-Whitney U test); MHCII, 3.04× ( P = .0019); and CD3, 4.4× ( P = .0104). To mimic off-target biopsy, samples from 2 mm 2 outside of inflammatory foci were analyzed, and these showed significant increases in Iba1 by 3.2× ( P = .0036, Mann-Whitney U test) and CD3 by 1.2× ( P = .0026). These data show diffusely increased immune response markers with canine myocarditis, with detection potentially independent of tissue sampling. Thus, endomyocardial biopsy and immunohistochemical detection of MHCII, CD3, and Iba1 may permit sensitive antemortem diagnosis of canine myocarditis.